Формування механізмів антикризового управління діяльністю підприємств: міжнародні економічні особлив - Кара, Н. І.; Атаманчук, З. А.; Курицький, В. Ю.; Kara, N.; Atamanchuk, Z.; Kurytskyi, V. (Видавництво Львівської політехніки, 2024)
Досліджено формування механізмів антикризового управління діяльністю під- приємств, зокрема розробка сценаріїв розвитку подій та планів дій на випадок їх реалізації, системи раннього попередження, оптимізація витрат, підвищення ефектив- ності виробництва, підготовка персоналу до роботи в кризових ситуаціях. Розглянуто визначення поняття “антикризове управління”, а також виокремлено цілі та основні завдання антикризового управління. Здійснено класифікацію чинників активізації антикризового управління на макро-, мезо- та мікрорівнях. Розглянуто міжнародний досвід антикризового управління підприємствами. Проаналізовано міжнародні еконо- мічні особливості формування та розвитку антикризового управління діяльністю під- приємств. Розглянуто застосування штучного інтелекту для проактивного управління ризиками з метою удосконалення антикризового управління, зокрема в прогнозуванні великих баз даних, прогнозі трендів, ідентифікації ризиків, створенні сценаріїв та автоматизації рутинних завдань. Зроблено висновок, що формування та розвиток ефективних механізмів антикризового управління є одним з найважливіших завдань для будь-якого підприємства, і, враховуючи міжнародні економічні особливості, підпри- ємства мають постійно адаптувати свої стратегії та інструменти для забезпечення сталого розвитку в умовах невизначеності.

Purpose. The purpose of the study was to analyze the mechanisms of anti-crisis management of the activities of enterprises in the conditions of international economic activity. The formation of mechanisms for anti-crisis management of enterprise activities was studied, in particular, the development of event development scenarios and action plans in case of their implementation, early warning systems, cost optimization, production efficiency improvement, personnel training for work in crisis situations. Design/methodology/approach. The definition of the concept of “anti-crisis management” is considered, as well as the goals and main tasks of anti-crisis management are highlighted. Classification of the factors of activation of anti-crisis management at the macro, meso and micro levels has been carried out. The international experience of anti-crisis management of enterprises is considered. The following research methods are used: analysis, synthesis, generalization, analogy, comparison, systematization. Findings.The international economic features of the formation and development of anti-crisis management of enterprise activities are analyzed. The use of artificial intelligence for proactive risk management with the aim of improving anti-crisis management, in particular in forecasting large databases, forecasting trends, identifying risks, creating scenarios and automating routine tasks, is considered. It was concluded that the formation and development of effective anti-crisis management mechanisms is one of the most important tasks for any enterprise, and, taking into account international economic features, enterprises must constantly adapt their strategies and tools to ensure sustainable development in conditions of uncertainty. Practical implications. In anti-crisis management, the use of AI allows to achieve the following results: improved forecasting – AI allows more accurate forecasting of risks and opportunities, which helps companies respond to market changes in a timely manner; optimization of resources – AI helps to optimize the use of resources, such as finances, personnel and materials, which allows to reduce costs and increase efficiency; increasing the speed of decision-making – AI allows you to quickly process large volumes of data and make informed decisions; improving the quality of customer service – AI allows personalizing interaction with customers, which increases their loyalty; increased competitiveness – companies that use AI can adapt more quickly to market changes and remain competitive. Originality/value. Modern trends in the field of anti-crisis management of enterprises include: proactive risk management (instead of reacting to crises that have already occurred, enterprises switch to proactive risk management, predicting them and taking measures to minimize them); use of technologies (artificial intelligence, machine learning and other technologies allow analyzing large volumes of data, identifying potential threats and making more informed decisions); cooperation with external experts (engagement of consultants and other specialists helps enterprises gain additional knowledge and experience in the field of anti-crisis management).
Formation of mechanisms for anti-crisis management of enterprises: international economic features
Keywords: антикризове управління; ризики; штучний інтелект; міжнародні економічні особливості; механізм антикризового управління; anti-crisis management; risks; artificial intelligence; international economic features; mechanism of anti-crisis management; D; 81; F47; 347.7; 339.9